Effects of self-efficacy promoting program combined with resistance exercise on pain and physical activity among patients with knee osteoarthritis - Glun-gumnird, Nareekarn; Nunthaitaweekul, Pachanut (Thai Journal of Nursing, 2023)
This quasi-experimental research aimed to study the effects of self-efficacy promoting program combined with resistance exercise on pain and physical activity among patients with knee osteoarthritis. Sixty patients with knee osteoarthritis, receiving care at the Orthopedics department, Thammasat University Hospital, were purposively selected and equally divided into a control group and an experimental group. Participants from both groups had similar characteristics in terms of Body Mass Index and severity of knee osteoarthritis. The experimental group received the self-efficacy promoting program combined with resistance exercise (n = 30) while the control group received usual nursing care (n = 30). The instruments consisted of the Numeric Rating Scale and the International Physical Activity Questionnaire (IPAQ-L). All instruments were examined for content validity by experts, and the reliability coefficients were 0.76 and 0.98 respectively. Data were analyzed using descriptive statistics and t-tests. The research findings were that 1) the experimental group had a lower mean score of pain than the control group, and the mean score of physical activity of the experimental group was greater than the control group (p < .05). 2) The experimental group had a lower mean score of pain than the usual nursing care, and the mean score of physical activity of the experimental group was greater than the usual nursing care. (p < .05).